Chapter Productivity? - Yes, but subject to sustainability! An evidence of (re)emergence of accounting for sustainability from the French agricultural authors from the XVII to the beginning of the XIX centuries - Altukhova-Nys, Yulia (Datini Studies in Economic History, 2023)
Five decades ago, first works and researches that have as title or subject « Envi-ronmental accounting », « Ecological accounting », or « Social accounting » have emerged. In these works, there are notably examples of accounting for strong sustainability approach in the agricultural sector. This paper searches for account-ing for sustainability premise in the French agricultural accounting literature of XVII-beginning of XIX centuries. It demonstrates that this literature presented some strong sustainability issues, although as a productivity and innovation dif-fusion condition, even earlier that the term of "accounting for sustainability" ex-isted.